The Effective English Instructional Practices Used in Students Learning English in Esp Listening Class at University of Muhammadiyah Malang - Tyas, RositaAgustining (Sebelas Maret University, 2016)
Listening is the language modality that is used most frequently. It has become the foundation of a numberof theories of second language acquisition that focus on the beginning levels of second languageproficiency. EFL and ESP differ not only in the nature of the learner, but also in the scope of the goals ofinstruction. Whereas in EFL all four language skills; listening, reading, speaking, and writing, are stressedequally, in ESP a needs assessment deter-mines which language skills are most needed by the students,and the program is focused accordingly. This study aims at focusing on a particular group of teachers inone of formal institution, that is, LC (language Center) of UMM (University of Muhammadiyah malang).The data collection was done through interviewing the three English teachers and conducting observationin the classes taught by the teachers. Also, some documentation are taken as a proof, they are in form ofinterview recordings, video recordings and photos. Based on the findings and discussions, the writersfound that there are some effective English instructional practices used in students learning English inESP listening class at UMM; namely cooperative learning, non-linguistic representations, and generatingand testing hypothesis. It can be revealed from studentsâ active participation through classroom discussionwhere they have to incorporate of sounds and images using symbols to represent relationships, predict andgenerate questions and hypotheses about the topic using limited resources, apply appropriate use of socialskills, face-to-face interaction, and individual and group accountability. These strategies are proven to beeffective in raising studentsâ active participation, interest, and motivation in ESP listening class. Inaddition, it assists the teachers to deliver the materials and information smoothly.